Bibliometric Analysis in the Realm of Character Education Management in the School Environment - Nanny Mayasari; Dedi Gunawan Saputra; Asri Widiatsih; Yulian Purnama (West Science Business and Management, 2023)
Character education management plays a pivotal role in fostering ethical, responsible, and well-rounded individuals within the school environment. This study employs bibliometric analysis, with a focus on VOSviewer visualization, to examine the scholarly landscape of character education management. A diverse set of databases was utilized, and a systematic search strategy was developed to identify relevant articles. The analysis encompasses publication trends, influential authors, citation networks, keyword co-occurrence, and thematic clusters. Key findings include a surge in character education research, prominent journals, prolific authors, and emerging trends such as the integration of character education with social-emotional learning and global citizenship education. Highly cited works offer foundational guidance, while thematic clusters highlight distinct research areas. This study contributes to a deeper understanding of character education management, offering insights for educators, policymakers, and researchers to enhance character development practices in schools.